PELAKSANAAN SUPERVISI KEPALA SEKOLAH DALAM PENERAPAN KURIKULUM 2013 DI SMA - Rita Candra Kasih (UNIVERSITAS BENGKULU, 2015)
The purpose of this study was to describe the implementation of the supervision and efforts to overcome obstacles in the implementation of K-13. This study is a qualitative research.Data collection techniques are interviews, observation, ocumentation. The data analysis technique is interactive analysis flow. The results of this study are: (1) the implementation of the supervision in the application of K-13 based on the condition many teachers have difficulty in implementing the curriculum and the limited facilities; (2) obstacles faced, among others: complexity of the task,lack of teacher preparation, high subjectivity, change of principal. (3) efforts to overcome the obstacles, among others: delegation of the senior teachers, motivation, guidance, coordination.Keywords: supervision, principals, curriculum 2013